Proactive review by the emergency department before inter‐hospital transfer (the PREVENT study). (7th July 2019) - Mitra, Biswadev; Carter, Annie; Smit, De Villiers; Rahman, Fatima; O'Donovan, Shane; Olaussen, Alexander; Pui, Jiun Kae; Abetz, Jeremy; Hunter, Peter; Cameron, Peter A
Abstract: Objectives: To determine the population of patients where patient transfer may be prevented by assessment of a senior ED registrar at the referring hospital. Methods: Patients transferred from Caulfield Hospital, specialising in community services, rehabilitation, aged care and aged mental health to The Alfred Emergency and Trauma Centre, an adult major referral centre within the same clinical network were identified from 1 July 2016 to 31 December 2016. Medical records were reviewed independently by two clinicians to determine preventability of transfer and whether attendance by a senior ED registrar could have prevented the transfer. Results: There were 221 patients included with a mean age of 73.6(15.1) years. The median time spent in the ED was 4 h (interquartile range 2–8) and 197 (89.1%) were admitted. There were 107 (48.6%) transfers deemed preventable or potentially preventable, with 104 preventable by attendance of a senior ED registrar. The most common indication for transfer was acute trauma ( n = 55; 24.9%), and the odds of a case being preventable or potentially preventable if transferred for the primary indication of trauma was 3.9 (95% confidence interval 2.1–7.1; P < 0.001). Among the preventable cases, the total cost of transfer was AU$105 984 over 6 months, not accounting for the costs of duplication of care. Conclusions: This proof‐of‐concept study suggests that strategies to expand the provision of acute care to outreach within specialist networks and reduce patient transfers should be further explored. An outreach programme for improved acute assessment of patients at the referring hospital particularly after acute trauma may prevent transfers, improving care pathways.